Licentiate Degree in Rural Education: contributions to training monitors of Agricultural Family Schools - Diego Gonzaga Duarte da Silva; Lourdes Helena da Silva (Universidade Federal do Norte do Tocantins, 2018)
The licentiate degrees in Rural Education are a recent achievement in our society and have been arising from the protagonist of the peasant social movements and trade unions. They had their expansion marked by the announcement MEC/SESU/SETEC/SECADI n.º 02/2012, which enabled the creation of new training courses for rural educators in 42 Brazilian Education Institutions. Considering these licentiate degrees, we highlight the Licentiate in Rural Education of the Federal University of Viçosa (LICENA), which in its creation and institutionalization process had the involvement and participation of diverse social and union movements. Among them, the Agricultural Family Schools (EFAs) have become a partner in the construction of the training processes of the course, as much by the experience with the Pedagogy of Alternating, as by the necessity of the initial formation of its monitors. Aiming to understand LICENA's training processes, we analyzed the evaluations of the monitors on the contributions of the course to the pedagogical practices developed in the EFAs, by conducting interviews that were submitted to the Content Analysis method. The results indicate that LICENA has contributed to the formation of the monitors both through the appropriation of didactic-pedagogical knowledge and through the stimulation of interdisciplinary practices.